2007
DOI: 10.1200/jco.2007.10.8993
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and Risk Factors for Elevated Infertility Concern in 10-Year Hematopoietic Cell Transplant Survivors and Case-Matched Controls

Abstract: The prevalence of infertility and related concerns is higher among long-term SCT survivors than among age-, sex-, and education-matched controls. Younger SCT recipients and those without children have persistent fertility-related needs even 10 years after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 21 publications
(26 reference statements)
5
59
0
Order By: Relevance
“…The potential for abnormal development, infertility, and sexual dysfunction is a source of significant emotional distress for survivors. [1][2][3] Recognizing treatment-associated risks and educating survivors and providers about potential reproductive complications is a key component of follow-up care. The Children's Oncology Group (COG) developed clinical practice guidelines to aid the assessment of survivors of childhood and adolescent cancers for long-term complications.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for abnormal development, infertility, and sexual dysfunction is a source of significant emotional distress for survivors. [1][2][3] Recognizing treatment-associated risks and educating survivors and providers about potential reproductive complications is a key component of follow-up care. The Children's Oncology Group (COG) developed clinical practice guidelines to aid the assessment of survivors of childhood and adolescent cancers for long-term complications.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the regimens used for allogeneic stem cell conditioning cause the most severe damage, especially in the case of total body irradiation (TBI), with POF and infertility almost constantly occurring in adults and in up to 81% of cases in children. 29,30 Pregnancies have been reported after conditioning with BEAM (carmustine, etoposide, cytarabine, melphalan) and autologous transplantation. A recent report from the Late Effects Working Committee of the Center for International Blood and Marrow Transplant Research (CIBMTR) concluded that some patients who received TBI and/or myeloablative conditioning can preserve their fertility.…”
Section: Treatments Of Refractory Lymphoma or Relapses And Second-linmentioning
confidence: 99%
“…53 Only a minority of AYA cancer survivors has reported satisfaction with the fertility information they received from their providers. 47,48,[63][64][65] Among those with low satisfaction with fertility information received, there is also a low expectation for quality of life outcomes around relationships and fertility. 19 Patients have identified a desire to be told accurate information about their prognosis and their risks and to play a contributing role in their treatment decisions.…”
Section: Practice Guidance For Fertility Preservationmentioning
confidence: 99%